Feasibility, Safety, and Effectiveness of Telerehabilitation in Mild-to-Moderate Parkinson's Disease - Bianchini, Edoardo; Onelli, Camilla; Morabito, Carmen; Alborghetti, Marika; Rinaldi, Domiziana; Anibaldi, Paolo; Marcolongo, Adriano; Salvetti, Marco; Pontieri, Francesco E. (Frontiers in Neurology, 2022)
Parkinson’s Disease (PD) patients frequently engage rehabilitation to ameliorate symptoms. During COVID-19 pandemic, access to rehabilitation programs has been markedly limited, consequently telerehabilitation gained popularity. In this prospective, open-label, pilot study, we aimed to investigate feasibility, safety and efficacy of telerehabilitation in mild-to-moderate PD patients. Twenty-three PD patients, with Hoehn & Yahr stage <3, without gait disturbances or dementia and capable of using a televisit platform, were recruited for a 5-week telerehabilitation program, consisting of 1 remote visit with a therapist and a minimum of 2 sessions of >30-min of self-conducted exercises per week. Patients received video tutorials of exercises and were asked to keep a diary of sessions. At baseline (T0), at the end of the intervention (T1), and 1 month after the end of treatment (T2) patients were remotely assessed with MDS-UPDRS part I-III, PDQ-39, FIM and Frontal Assessment Battery scales. Acceptable compliance to the program was defined as >60% matching of frequency and duration of sessions, whereas optimal compliance was set at >80% matching. Dropout rate was 0%. Over 85% of patients reached acceptable adherence cut-off and around 70% reached optimal one. No adverse events were reported during sessions. rANOVA showed significant effect of factor “time” for MDS-UPDRS-III (p < 0.0001) with a mean reduction of 4.217 points between T0 and T1 and return to baseline at T2. No significant effect was found for other outcome measures. Our findings demonstrate that telerehabilitation is safe, feasible and effective on motor symptoms in mild-to-moderate PD patients.